Perspective of Cappuccino Cincau Sellers on Trademark Rights in South Banjarmasin Sub-District - Uswatun Hasanah; Hidayatul Husna; Dini Awwalia; Muhammad Noor Ridani; Muhammad Haris (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
ABSTRACT The right to a trademark is a special right that has been granted by the state to the holder of a trademark that has been recorded within a certain period of time by using the trademark itself or allowing others or using the trademark. There are still many people who do not know the use of the right to trademark. Due to the limited extension activities and awareness raising from the authorities about the usefulness of intellectual property rights, especially the right to trademark, until the business people only know that trademark registration must be done with the payment of expensive and complicated in the management. Though the trademark is very important, the trademark is used for identity, legal protection, and distinguish the goods or services produced. This study uses empirical legal research methods. The results of the analysis obtained it turns out that there are still many Cappuccino Cincau entrepreneurs who have not registered the trademark. This is because the seller lacks understanding of trademark rights and the seller feels no need to register the trademark for reasons of time-consuming and complicated management. Keywords : Intellectual Property Rights, Trademark Rights, Entrepreneur Perspective. ABSTRAK Hak pada merek ialah hak khusus yang telah diberikan oleh negara pada pemegang merek yang telah tercatat dalam rentang waktu tertentu dengan penggunaan merek itu sendiri atau mengizinkan orang lain atau menggunakan merek tersebut. Masih banyak masyarakat yang belum mengetahui peggunaan hak atas merek. Karena terbatasnya kegiatan penyuluhan dan peningkatan kesadaran dari pihak yang berwenang tentang kegunaan hak kekayaan intelektual, khususnya hak atas merek, hingga para pelaku usaha hanya mengetahui bahwa pendaftaran merek harus dilakukan dengan pembayaran yang mahal dan rumit dalam pengurusanya. Padahal merek sangatlah penting, merek ini digunakan untuk identitas, perlindungan hukum, dan membedakan barang atau jasa yang dihasilkan. Dalam pengumpulan data pada percobaan ini memakai cara atau metode empiris danxkepustakaan. Hasil analisa yang diperoleh masih banyak penjual usaha Cappucino Cincau yang belum mendaftarkan mereknya. Hal ini dikarenakan penjual kurang memahami hak merek dan penjual merasa tidak perlu mendaftarkan mereknya karena alasan pengurusan yang memakan waktu dan rumit. Kata Kunci : Hak Kekayaan Intelektual, Hak Merek, Perspektif Pengusaha.